The effects of systemic risk in Portugal: A CoVaR approach - Ferreira, Bárbara Mendes (2020)
The Great Recession in the context of financial globalization raised the interest in systemic risk's measurement. The main goal of this dissertation is the study of systemic risk dynamics in the Portuguese financial system between 02/06/2003 and 30/06/2020. Specifically, we analyze the impact of Portuguese banks distress on the domestic financial system as well as the repercussions of a crisis in the Portuguese financial system on domestic banks. For that purpose, we use ΔCoVaR systemic risk measure. Furthermore, the bootstrap KS test is applied to determine the statistical accuracy of the ΔCoVaR forecasts and to rank banks according to their systemic importance and systemic vulnerability. Throughout this dissertation alternative methodologies to obtain banks returns and to estimate VaR are applied to analyze the sensitivity of VaR and ΔCoVaR forecasts. The empirical results reveal that no Portuguese bank is considered systemic important or vulnerable in the analyzed period. However, considering the studied banks, all of them present its highest contribution to the financial system's systemic risk and its highest vulnerability to the system's shocks in the context of the Great Recession. Furthermore, BES and BNF are more vulnerable to the Portuguese financial system's impact in the last phase of their life cycles. Additionally, from 02/06/2003 to 13/10/2010, BCP is the bank with the major contribution to the financial system's systemic risk and the most vulnerable to system's shocks. Finally, VaR and ΔCoVaR estimates reveal sensitivity to the banks returns computation methodology as well as to the VaR model used.